A Model for Apoptotic-Cell-Mediated Adaptive Immune Evasion via CD80–CTLA-4 Signaling - Yakoub, Abraam M.; Schülke, Stefan (Frontiers in Pharmacology, 2019)
Apoptotic cells carry a plethora of self-antigens but they suppress eliciting of innate and adaptive immune responses to them. How apoptotic cells evade and subvert adaptive immune responses has been elusive. Here, we propose a novel model to understand how apoptotic cells regulate T cell activation in different contexts, leading mostly to tolerogenic responses, mainly via taking control of the CD80–CTLA-4 coinhibitory signal delivered to T cells. This model may facilitate understanding of the molecular mechanisms of autoimmune diseases associated with dysregulation of apoptosis or apoptotic-cell clearance, and it highlights potential therapeutic targets or strategies for treatment of multiple immunological disorders.